The 70‐year search for the voltage‐sensing mechanism of ion channels. (6th July 2022) - Catacuzzeno, Luigi; Franciolini, Fabio
Abstract: This retrospective on the voltage‐sensing mechanisms and gating models of ion channels begins in 1952 with the charged gating particles postulated by Hodgkin and Huxley, viewed as charges moving across the membrane and controlling its permeability to Na + and K + ions. Hodgkin and Huxley postulated that their movement should generate small and fast capacitive currents, which were recorded 20 years later as gating currents. In the early 1980s, several voltage‐dependent channels were cloned and found to share a common architecture: four homologous domains or subunits, each displaying six transmembrane α‐helical segments, with the fourth segment (S4) displaying four to seven positive charges invariably separated by two non‐charged residues. This immediately suggested that this segment was serving as the voltage sensor of the channel (the molecular counterpart of the charged gating particle postulated by Hodgkin and Huxley) and led to the development of the sliding helix model. Twenty years later, the X‐ray crystallographic structures of many voltage‐dependent channels allowed investigation of their gating by molecular dynamics. Further understanding of how channels gate will benefit greatly from the acquisition of high‐resolution structures of each of their relevant functional or structural states. This will allow the application of molecular dynamics and other approaches. It will also be key to investigate the energetics of channel gating, permitting an understanding of the physical and molecular determinants of gating. The use of multiscale hierarchical approaches might finally prove to be a rewarding strategy to overcome the limits of the various single approaches to the study of channel gating. Abstract : Abstract figure legend Time line of our understanding of the voltage‐sensing mechanisms and gating models of voltage‐dependent channels from the charged gating particles postulated by Hodgkin and Huxley in 1952, later visualized as the gating currents, subsequently identified with the fourth segment (S4) as their molecular counterpart within the sliding helix model, then observed in the crystallographic structures of the voltage‐dependent channels, and currently investigated by simulations of molecular dynamics.